2022
DOI: 10.3390/su14031859
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Analysis on Influence of Natural Airflow on Spent Fuel Heat Removal in Dry Cask Storage

Abstract: A key issue contributing to the success of NPP technology is the safe handling of radioactive waste, particularly spent nuclear fuel. According to the IAEA safety standard, the spent fuel must be stored in interim wet storage for several years so the radiation and the decay heat of the spent fuel will decrease to the safe limit values, after which the spent fuel can be moved to dry storage. In this study, we performed a theoretical analysis of heat removal by natural convection airflow in spent nuclear fuel dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Induksi udara yang dialirkan pada saluran (air gap) mempengaruhi aliran udara apung (bouyancy), sehingga mempercepat pembuangan panas dry cask storage [11]. Ratiko, dkk melakukan analisis terkait heat removal dry cask storage, menggunakan contam software model aliran udara dalam air gap dapat mudah diketahui [12]. Alyokhina, S. dkk menganalisis struktur aliran di dalam wadah berventilasi dengan simulasi numerik, mekanisme utama perpindahan panas dan massa yang mengambil bagian dalam pendinginan bahan bakar nuklir bekas dapat mudah diketahui [13].…”
Section: Pendahuluanunclassified
“…Induksi udara yang dialirkan pada saluran (air gap) mempengaruhi aliran udara apung (bouyancy), sehingga mempercepat pembuangan panas dry cask storage [11]. Ratiko, dkk melakukan analisis terkait heat removal dry cask storage, menggunakan contam software model aliran udara dalam air gap dapat mudah diketahui [12]. Alyokhina, S. dkk menganalisis struktur aliran di dalam wadah berventilasi dengan simulasi numerik, mekanisme utama perpindahan panas dan massa yang mengambil bagian dalam pendinginan bahan bakar nuklir bekas dapat mudah diketahui [13].…”
Section: Pendahuluanunclassified
“…The study of dry cask design for spent nuclear fuels generated from RSG GAS has been reported [11]. Stainless steel and aluminum (Al) are the candidate materials that were considered for the canister.…”
Section: Introductionmentioning
confidence: 99%